2014
DOI: 10.1007/s10875-014-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel NFKB2 Mutation in Early-Onset CVID

Abstract: Common variable immunodeficiency (CVID) is heterogeneous, clinically, immunologically and genetically. The majority of genetic mechanisms leading to CVID remain elusive. We studied a Greek Cypriot family of non-consanguineous parents. Two children were diagnosed with CVID at an early age. Whole exome sequencing revealed 8bp deletion in the C-terminal part of NFKB2 gene associated with disease. The mutation leads to a frameshift (p.Asp865Valfs*17) altering 17 C-terminal amino acids from residue 865, and creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 10 publications
1
58
0
Order By: Relevance
“…59 In addition, NFKB2 haploinsufficiency has been acknowledged as the disease-causing mechanism of CVID-associated NFKB2 mutations. [46][47][48][49][50][51] Furthermore, several reports have supported a functional haploinsufficiency as the predominant disease mechanism associated with various primary immunodeficiencies and autoimmune phenotypes caused by mutations in TACI, 60,61 CTLA4, 15,62 NFAT5 63 (MIM: 04708), VAV1 64 (MIM: 164875), GATA2 65 (MIM: 137295), and others. Thus haploinsufficiency, frequently associated with incomplete penetrance, appears as a recurrent paradigm and emphasizes the requirement for accurate gene regulation within the immune system.…”
Section: Maintenance Of Residual Nf-kb1 Function Through Decay Of Thementioning
confidence: 97%
“…59 In addition, NFKB2 haploinsufficiency has been acknowledged as the disease-causing mechanism of CVID-associated NFKB2 mutations. [46][47][48][49][50][51] Furthermore, several reports have supported a functional haploinsufficiency as the predominant disease mechanism associated with various primary immunodeficiencies and autoimmune phenotypes caused by mutations in TACI, 60,61 CTLA4, 15,62 NFAT5 63 (MIM: 04708), VAV1 64 (MIM: 164875), GATA2 65 (MIM: 137295), and others. Thus haploinsufficiency, frequently associated with incomplete penetrance, appears as a recurrent paradigm and emphasizes the requirement for accurate gene regulation within the immune system.…”
Section: Maintenance Of Residual Nf-kb1 Function Through Decay Of Thementioning
confidence: 97%
“…Nuclear factor of kappa light polypeptide gene enhancer in B-cells 2 (NFKB2) is a pleiotropic transcription factor present in almost all cell types but its precise roles remain incompletely understood. Two other groups also reported NFKB2 mutations in patients with similar phenotypes making the involvement of NFKB2 in DAVID syndrome highly likely even if the endocrine phenotype was not systematically studied (10,11). However the precise mechanisms whereby this factor may lead to endocrine deficits remain unclear.…”
Section: David Syndrome and Nfkb2mentioning
confidence: 99%
“…The genes and the pathways identified in this study may be further pursued by studies with larger sample size and functional studies. In addition to whole genome-sequencing, recently exome-sequencing identified additional mutations that are related or causative in individual CVID patients, such as the newly identified mutations in genes NLRP12 [53], NFKB2 [54], ITPKB [55] and RAG1 [56]. A recent genetic study using whole exome-sequencing and comparative genomic hybridization array identified multiple heterozygous mutations and deletions in gene IKZF1 responsible for a form of CVID with drastically reduced number of B cells.…”
Section: Whole Genome Sequencing and Rna Sequencingmentioning
confidence: 99%